2020
DOI: 10.3390/antiox9090848
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Mitochondria Inter-Talk: A Potential Therapeutic Strategy in Obesity and Type 2 Diabetes

Abstract: The rising prevalence of obesity and type 2 diabetes (T2D) is a growing concern worldwide. New discoveries in the field of metagenomics and clinical research have revealed that the gut microbiota plays a key role in these metabolic disorders. The mechanisms regulating microbiota composition are multifactorial and include resistance to stress, presence of pathogens, diet, cultural habits and general health conditions. Recent evidence has shed light on the influence of microbiota quality and diversity on mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 144 publications
0
23
0
Order By: Relevance
“…In recent years, our understanding of the role played by mitochondria during this kind of challenge has expanded far beyond its bioenergetic capacity, which is represented by well characterized pathways such as oxidative phosphorylation (OXPHOS), fatty acid β-oxidation (FAO) and the tricarboxylic acid (TCA) cycle (Pfanner et al, 2019). Indeed, it is now widely accepted that mitochondria regulate cytosolic calcium homeostasis and cellular redox status, that they generate much of the cell reactive oxygen species (ROS), and that they are involved in steroid and heme biosynthesis, urea degradation, apoptosis and initiation of inflammation through inflammasomes (Chinnery and Hudson, 2013;Wong et al, 2016;Jackson and Theiss, 2020;Vezza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our understanding of the role played by mitochondria during this kind of challenge has expanded far beyond its bioenergetic capacity, which is represented by well characterized pathways such as oxidative phosphorylation (OXPHOS), fatty acid β-oxidation (FAO) and the tricarboxylic acid (TCA) cycle (Pfanner et al, 2019). Indeed, it is now widely accepted that mitochondria regulate cytosolic calcium homeostasis and cellular redox status, that they generate much of the cell reactive oxygen species (ROS), and that they are involved in steroid and heme biosynthesis, urea degradation, apoptosis and initiation of inflammation through inflammasomes (Chinnery and Hudson, 2013;Wong et al, 2016;Jackson and Theiss, 2020;Vezza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In obese individuals, proinflammatory bacteria can extract more energy from the diet compared to healthy lean controls [ 193 ]. Reduced anti-inflammatory bacteria are linked to disturbed short-chain fatty acid (SCFA) production (such as propionate, butyrate, acetate as the results of microbial degradation of fibers) having an otherwise beneficial effect on host metabolism, especially insulin sensitivity through regulating mitochondrial metabolism of peripheral tissues and thus keeping redox homeostasis [ 194 , 195 ]. The effect of SCFA, which enters the cells through FFA2/GPR43 and FFA3/GPR41 receptors, on β-cells is rather controversial [ 196 ].…”
Section: Dysbalanced Redox Homeostasis Contributing To β-Cell Dysfunction Under Metabolic Stressmentioning
confidence: 99%
“…The major diseases are prevented by the developments in human body. Studies revealed that animal models and in adults had demonstrates that microbiota improper function can lead to the development of obesity in type 2 diabetic patients.There are chances of fluctuation in the energy level of healthy individuals these inhibits the insulin resistant and and develops dyslipidemia are developed by low anti-bacterial activity [9] . Thiazolidinediones: These Troglitazone has been found in the year 1997 in the type 2 diabetes milletus.…”
Section: Therapeutic Drugs For Type II Diabetes Mellitusmentioning
confidence: 99%